Implementation of SIAPIK for MSMEs for Transaction Recording and Financial Statement Preparation in Paguyuban Village, Way Lima Subdistrict, Pesawaran Regency - Metalia, Mega; Septiyanti, Ratna; Yuniati, Ati (Indonesian Journal of Community Services Cel, 2025)
Background: Paguyuban Village, Way Lima District, Pesawaran Regency, Lampung Province, has significant potential in various sectors such as manufacturing, agriculture, fisheries, and others. However, this potential is not matched by public knowledge regarding financial records, such as the exclusion of personal assets from business activities and poor record-keeping and bookkeeping. As a result, MSMEs struggle to determine their revenue and obtain credit from relevant financial institutions.It is not easy for MSMEs to obtain credit financing from banks or non-bank institutions because their financial statements are not available.Aims: This community service is carried out by introducing and training MSME actors on the SIAPIK application for recording and preparing financial reports.Method: This training was conducted using a Focus Grub Discusion (FGD) through lectures, discussions, and simulations of how to use the SIAPIK application, resulting in qualitative data.Results: The SIAPIK application training showed that MSME actors better understand the importance of financial statements. The result of this activity was an increase in MSME owners' knowledge regarding recording business financial transactions using the SIAPIK application, from 49% to 97%.